2016
DOI: 10.1590/1516-3180.2015.01332210
|View full text |Cite
|
Sign up to set email alerts
|

Mistreatment in an academic setting and medical students' perceptions about their course in São Paulo, Brazil: a cross-sectional study

Abstract: Mistreatment in an academic setting and medical students' perceptions about their course in São Paulo, Brazil: a cross-sectional study Maus-tratos ABSTRACTCONTEXT AND OBJECTIVE: High prevalence of mistreatment among medical students has been described in the worldwide literature since the 1980s. However, studies addressing the severity and recurrence of victimization and its effects on students' perceptions of their medical course are scarce. This study had the aim of estimating the prevalence of exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
1
6
0
5
Order By: Relevance
“…52 There were 16 523 consultant and trainee respondents to surveys that separated results by level of training (online supplemental table S2). A greater proportion of medical students experienced psychiatric distress (72.9%; reported in 2 studies) 52 59 than residents (40.8%; reported in 6 studies) 17 Open access in 4 studies). 43 47 71 73 A greater proportion of residents endorsed loss of career opportunities (35.0%; reported in 3 studies) 55 65 72 compared with medical students (16.0%; reported in 3 studies) 13 15 52 and consultants (30.6%; reported in 8 studies).…”
Section: Definition Of Academic Bullyingmentioning
confidence: 99%
“…52 There were 16 523 consultant and trainee respondents to surveys that separated results by level of training (online supplemental table S2). A greater proportion of medical students experienced psychiatric distress (72.9%; reported in 2 studies) 52 59 than residents (40.8%; reported in 6 studies) 17 Open access in 4 studies). 43 47 71 73 A greater proportion of residents endorsed loss of career opportunities (35.0%; reported in 3 studies) 55 65 72 compared with medical students (16.0%; reported in 3 studies) 13 15 52 and consultants (30.6%; reported in 8 studies).…”
Section: Definition Of Academic Bullyingmentioning
confidence: 99%
“…En estas dinámicas, la jerarquía proporciona una cadena de mando en la que algunas personas son las responsables de tomar decisiones médicas complejas así el equipo bajo su mando hace efectivo el plan encaminado a salvar la vida o en ARS MEDICA Revista de Ciencias Médicas Volumen 46 número 4 año 2021 general a prestar un mejor servicio. El maltrato en las escuelas de medicina latinoamericanas (Iglesias et al, 2005;Maida et al, 2006;Castrillón et al, 2010;Paredes et al, 2010;Bastías-Vega et al, 2011;Guevara-Cuellar et al,2011;Silva-Villareal et al, 2013;Bermeo et al, 2015;Mejia et al,2015;Millán et al,2015;Munayco-Guillén et al, 2015;Peres et al, 2016;Fretes et al, 2016;Sánchez et al, 2016;Derive et al, 2017;Mariscal et al, 2017;Martínez & Henríquez, 2018;Gali et al, 2019;Reyes-Arellano et al, 2019) parece tener la Tabla 1: Caracterización de conductas de maltrato, amenaza, acoso, discriminación y violencia de género en facultades de medicina latinoamericanas.…”
Section: Contexto Latinoamericanounclassified
“…Recently, several studies have addressed this issue and found that medical trainee harassment and discrimination is a widespread phenomenon and has not declined over time. In a study published in 2016, Peres et al 14 conducted a cross-sectional study of mistreatment in a medical academic setting in Brazil. Three hundred and seventeen students from the first to the sixth year completed an anonymous web-based survey in which high prevalence of mistreatment was found.…”
Section: Introductionmentioning
confidence: 99%